Green infrastructure planning in Germany and China. A comparative approach to green space policy and planning structure. - Hu, Tinghao; Chang, Jiang; Syrbe, Ralf-Uwe (My University, 2020)
Green Infrastructure (GI) provides an important life-support system for regions and cities. Inspired by, supported by or copied from nature, GI is intended to deal with issues that traditional grey infrastructure can hardly accomplish. Initiated by the European Union’s (EU) Biodiversity Strategy, Germany was an early adopter and thus a role model for the GI approach. In particular, a systematic GI planning system composed of formal and informal planning instruments has been established and implemented from the national to the local level. In comparison, China has not yet officially issued guidance or laws for GI planning. Instead, GI implementations are mainly concentrated at the urban and local scale in the form of green municipal engineering. Scrutinizing the spatial planning system in China, however, we can identify a top-down “5+1” model as a GI planning framework. This includes five types of statutory and non-statutory planning together with the garden city movement. Germany may benefit from China’s diversified and inclusive GI development model and its efforts to promote regional transformation and enhance citizens’ sense of pride in their city. On the other hand, China can learn from Germany’s integrated GI planning system and top-level design. Due to the cross-cutting nature of the issues involved, China’s national spatial planning system must be reformed in order to improve GI planning in the country. The aim of this paper is to compare GI planning in Germany and China, two countries at different developmental stages and with contrasting social and governmental systems.
Keywords: Grünraumplanung; Raumplanung; Stadtplanung; Regionalplanung; Planungssystem; Systemvergleich; Internationaler Vergleich; Grüne Infrastruktur